ISLAMIZATION OF KNOWLEDGE AND ITS CHALLENGE - Nisa, Ulfatun Wahidatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The contribution of Islamic thought to world civilization has been openly, objectively and sympathetically acknowledged by Western scholars. However, the glory of Islamic civilization has now passed, leaving only the nostalgia of historical beauty. Little by little, Muslims began to experience decline and weakness in various fields. In order to maintain their Islamic identity, there is a tendency for Muslims to be defensive and exclusive. This happens, for example, in some Islamic boarding schools and madrassas that tend to only emphasise the study of Islamic Knowledge the loss of the sacred aspect of the concept of general knowledge and the defensive attitude toward Muslim Knowledge causes stagnation. This is dangerous for the development of Islamic Knowledge. Therefore, an idea emerged to bring together the advantages of the two, so that a new modern Knowledge was born but still religious and relevant to the concept of tawhid, this idea is known as the Islamization of Knowledge. The method used in this research is library research, and the primary data source in this research is documented data from Muslim scholars on Islamization. While secondary data in this research is in the form of journals, books, and websites related to the research topic. The data analysis technique is done by reducing, presenting, and drawing conclusions. The findings of this research will be presented in the form of an overview of how far the relevance of Islamization of Knowledge its challenges, as well as some actions that can be taken to answer the challenges in the current era.